2018
DOI: 10.1002/jcb.28331
|View full text |Cite
|
Sign up to set email alerts
|

Role of the transforming growth factor‐β signaling pathway in the pathogenesis of colorectal cancer

Abstract: The transforming growth factor-β (TGF-β) signaling pathway plays an important role in cancer cell proliferation, growth, metastasis, and apoptosis. It has been shown that TGF-β acts as a tumor suppressor in the early stages of the disease, and as a tumor promoter in its late stages. Mutations in the TGF-β signaling components, the TGF-β receptors and cytoplasmic signaling transducers, are frequently observed in colorectal carcinomas. Exploiting specific TGF-β receptor agonist and antagonist with antitumor prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 93 publications
0
26
0
Order By: Relevance
“…TGF‐β1 is essential for the induction of EMT and regulating autophagy‐induced EMT. In conclusion, TGF‐β1‐induced EMT is inhibited by miR‐16 in NSCLC cells by activation of autophagy through regulating ATG3 …”
Section: Tumor Suppressor Micrornasmentioning
confidence: 87%
“…TGF‐β1 is essential for the induction of EMT and regulating autophagy‐induced EMT. In conclusion, TGF‐β1‐induced EMT is inhibited by miR‐16 in NSCLC cells by activation of autophagy through regulating ATG3 …”
Section: Tumor Suppressor Micrornasmentioning
confidence: 87%
“…Cancer progression is caused by several changes in oncogenes and tumor-suppressor genes during several years [42]. Numerous studies have indicated a main role for miRNAs in the cancer pathogenesis [42]. miRNAs can affect cancer progression through regulation of cell growth and apoptosis [42].…”
Section: Microrna and Cancer Developmentmentioning
confidence: 99%
“…Numerous studies have indicated a main role for miRNAs in the cancer pathogenesis [42]. miRNAs can affect cancer progression through regulation of cell growth and apoptosis [42]. The miRs are used as biomarkers for assessing cancer prognosis and drug efficacy [42].…”
Section: Microrna and Cancer Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…So, there is a need for developing new anticancer drugs to be used with conventional and newly introduced anticancer drugs for targeting multiple signaling pathways and making a reduction in the viability of cancer cells. It seems that plant‐derived chemicals with high antitumor activity are of interest due to their minimal side effects and multitargeting (Ashrafizadeh, Ahmadi, Farkhondeh, & Samarghandian, ; Ashrafizadeh et al, ; Ashrafizadeh et al, ; Khoshakhlagh et al, ; Soleimani et al, ; Soleimani et al, ; Tavakol et al, ).…”
Section: Introductionmentioning
confidence: 99%